MicroRNA-138 is a prognostic biomarker for triple-negative breast cancer and promotes tumorigenesis via TUSC2 repression - Nama, Srikanth (2020)
Breast cancer manifests as a spectrum of subtypes with distinct molecular signatures, and different responses to treatment. Of these subtypes, triple-negative breast cancer (TNBC) has the worst prognoses and limited therapeutic options. Here we report aberrant expression of microRNA-138 (miR-138) in TNBC. Increased miR-138 expression is highly specific to this subtype, correlates with poor prognosis in patients, and is functionally relevant to cancer progression. Our findings establish miR-138 as a specific diagnostic and prognostic biomarker for TNBC. OncomiR-138 is pro-survival; sequence-specific miR-138 inhibition blocks proliferation, promotes apoptosis and inhibits tumour growth in-vivo. miR-138 directly targets a suite of pro-apoptotic and tumour suppressive genes, including tumour suppressor candidate 2 (TUSC2). miR-138 silences TUSC2 by binding to a unique 5′-UTR target-site, which overlaps with the translation start-site of the transcript. Over-expression of TUSC2 mimics the phenotype of miR-138 knockdown and functional rescue experiments confirm that TUSC2 is a direct downstream target of miR-138. Our report of miR-138 as an oncogenic driver in TNBC, positions it as a viable target for oligonucleotide therapeutics and we envision the potential value of using antimiR-138 as an adjuvant therapy to alleviate this therapeutically intractable cancer.